Against comparativism about mass in Newtonian Gravity - a case study in the metaphysics of scale - Martens, N (2016)
This thesis concerns the metaphysics of scale. It investigates the implications of a physical determinable being dimensionful. In particular, it considers the case study of mass, as it features within Newtonian Gravity. Nevertheless, most of the terminology, methodology and arguments developed should be relatively straightforwardly applicable to other determinables and theories. Weak Absolutism about mass holds that mass ratios obtain in virtue of absolute masses. Weak Comparativism denies this. In the first five chapters I argue in favour of Weak Absolutism over Weak Comparativism. The sixth chapter argues against reducing mass to other non-mass facts. The overall conclusion is Strong Absolutism about mass within Newtonian Gravity: mass ratios obtain in virtue of absolute masses, which themselves are fundamental (i.e. they do not require anything further in order to obtain). Comparativism promises to recover all the virtues of absolutism, in particular its empirical adequacy, but at a lower 'metaphysical cost'. Special attention is given to Dasgupta's recent comparativist proposal. Dasgupta interprets the requirement of empirical adequacy in terms of the undetectability of the absolute mass scale. I argue that undetectability is an unsuitable way of understanding empirical adequacy and that we would do better to understand it in terms of a theory's ability to correctly generate the set of empirically possible worlds (or at least the actual world). I refute Dasgupta's comparativism both on my terms and on his own terms. I subsequently develop and strongly criticise alternative versions of comparativism. Chapter five sheds doubt on the supposed 'metaphysical parsimony' of comparativism. This debate should be of particular interest to readers who engage with the substantivalism-relationalism debate. These debates are much more entwined than previously acknowledged, which provides a significant source of mutual inspiration, although I do also draw out some important disanalogies.